Roles of Autophagy and Autophagy-Related Proteins in Antifungal Immunity - Kanayama, Masashi; Shinohara, Mari L. (Frontiers in Immunology, 2016)
Autophagy was initially characterized as a process to digest cellular components, including damaged cell organelles or unused proteins. However, later studies showed that autophagy plays an important role to protect hosts from microbial infections. Accumulating evidences showed the contribution of autophagy itself and autophagy-related proteins in the clearance of bacteria, virus, and parasites. A number of studies also revealed the molecular mechanisms by which autophagy is initiated and developed. Furthermore, it is now understood that some autophagy-related proteins are shared between two distinct processes; autophagy and LC3-associated phagocytosis (LAP). Thus, our understanding on autophagy has been greatly enhanced in the last decade. In contrast, roles of autophagy and autophagy-related proteins in fungal infections are still elusive relative to those in bacterial and viral infections. Based on limited numbers of reports, host responses including autophagy and autophagy-related proteins appear to significantly vary depending on invading fungal species. In this review, we discuss how autophagy and autophagy-related proteins are involved in antifungal immune responses based on recent discoveries.